Finger gangrene: an unusual presentation of leprosy - Galal El-Anany; Hanan Nada; Noha Nagui; Suzan Shalaby; Eman Sany; Naglaa Elmongy; Ahmed Nada (Wolters Kluwer Medknow Publications, 2019)
Peripheral gangrene is a rare presentation of some types of leprosy. We report a case of 16 years old male presented with history of fever of unknown origin followed by peripheral digital gangrene. Careful skin examination showed a hypopigmented anesthetic patch. Further investigations showed antiphospholipid syndrome positivity. What's the link between both diagnoses?